Peningkatan Kemandirian Peternak Kambing Lokal melalui IPTEK Pakan Wabitak yang Disuplementasi Tepung Rempah Andaliman (Zanthoxylum acanthopodium) - Wicaksana, Kunaifi; Silaban, Rikardo; Putri, Dwi Desmiyeni; Rais, Harfina; Aprilia, Lisa; Sugesti, Madyan (Universitas Pahlawan Tuanku Tambusai, 2026)
Goat farming is still carried out traditionally at Berkah Mandiri Farm (BMF) in Pesawaran Regency. Low livestock production is not only caused by the lack of knowledge of farmers regarding livestock maintenance but also due to the very scarce availability of superior forage. Optimization of agricultural waste as animal feed is expected to answer the urgency of providing scarce natural fiber sources, especially in Pejambon Village, Pesawaran Regency. In addition, the addition of prebiotic sources from Andaliman spices is expected to affect bioprocesses in the rumen and have an impact on reducing methane gas. This community service aims to provide alternative feed solutions for ruminant livestock to improve livestock businesses at Berkah Mandiri Farm, increasing the availability of sustainable feed through patent application tests of Complete Feed Formula supplemented with Andaliman Fruit Flour in alternative feed products, namely WABITAK (Livestock Biscuit Wafers). The results of the community service showed that responses agreed with the importance of innovation by 47%, the importance of technology by 52%, the need for alternative feed by 48% and control of wabitak production by 46%. It can be concluded that the breeders showed high enthusiasm and had the potential to conduct in-depth research studies, especially on the aspect of increasing productivity.